2017
DOI: 10.1016/j.bbagen.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fullerene on lipid bilayers displaying different liquid ordering: a coarse-grained molecular dynamics study

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…Slower diffusion was observed at higher fullerene concentrations in agreement with Sastre et al . 39 . Perhaps surprisingly, the differences in lateral fullerene diffusion in the three cases are very small.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Slower diffusion was observed at higher fullerene concentrations in agreement with Sastre et al . 39 . Perhaps surprisingly, the differences in lateral fullerene diffusion in the three cases are very small.…”
Section: Resultsmentioning
confidence: 99%
“…The coarse grained fullerene molecule (F16) consist of 16 beads and the latest updated fullerene parameters were used to reproduce the atomistic potential of mean force (PMF) profile of transferring a fullerene through a lipid membrane 49 . This fullerene model has been previously validated against experimental solvation free energies and atomistic simulations and it has been used in numerous independent studies with various lipid bilayers (DPPC, POPC, DOPC, DSPC and DUPC) and shown to work well 14,19,21,28,34,39,42,4953 . The models and atom numberings are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] for details). A large variety of lipid membrane phenomena have been successfully investigated using the Martini force field [26], in some cases also by involving the interaction with carbon-based nanomaterials [27].…”
Section: Coarse-grained Descriptionmentioning
confidence: 99%